Analisis Implementasi Good Governance dalam Pengelolaan Sumber Daya Manusia di Organisasi Sektor Publik: Analysis of Good Governance Implementation in Human Resource Management in Public Sector Organizations - Faridawati Faridawati (Program Studi Manajemen Keuangan Sektor Publik, Politeknik Wahdah Islamiyah Makassar, 2026)
The implementation of good governance in human resource management (HRM) within public sector organizations plays an important role in improving the quality of human resources to achieve organizational objectives. This study aims to analyze and understand the implementation of good governance in HRM in public sector organizations and to identify the factors influencing its implementation. The research employs a qualitative approach using a literature review method and descriptive analysis of policies, regulations, and human resource management practices in public sector organizations. The results indicate that the implementation of good governance in HRM can enhance the professionalism of public officials’ performance and improve the quality of public services. However, several challenges remain, including a lack of transparency and accountability, limited human resource capacity, and weak internal supervision systems. The factors influencing the implementation of good governance include government policies, organizational structure, organizational culture, and human resource competencies. Therefore, strong leadership commitment, strengthened supervision systems, and continuous improvement of officials’ competencies are required to ensure the optimal application of good governance principles in human resource management within public sector organizations.